The effects of Mn and/or Ni dopants on the in vitro/in vivo performance, structural and magnetic properties of ?-tricalcium phosphate bioceramics - Ates, Tankut; Dorozhkin, Sergey, V; Kaygili, Omer; Kom, Mustafa; Ercan, Ismail; Bulut, Niyazi; Ince, Turan (Elsevier Sci Ltd, 2019)
The present study describes the effects of dopants of Mn and/or Ni on the structural, magnetic and in vivo/in vitro performances of beta-tricalcium phosphate (beta-TCP) bioceramics synthesized by a sol-gel method. Both types of dopants caused significant effects on the structure-related parameters of beta-TCP, including the crystallite dimensions and lattice parameters. The magnetic properties of as-prepared samples were found to be affected by the type and amount of the dopant(s). The in vitro antimicrobial activities of doped beta-TCPs against American Type Culture Collection (ATCC) reference bacterial and fungal strains were evaluated. Among them, only 1.35Ni-TCP displayed an effective antimicrobial activity against Gram-positive bacteria (50 mu g/mL Minimum Inhibitory Concentration (MIC) range), while other types of doped beta-TCPs did not possess with such effect. The in vivo tests showed that each formulation could be a good nominate for bone healing and bone treatment.
Keywords: beta-tricalcium phosphate; Dopants; Magnetic properties; In vitro; In vivo